2014
DOI: 10.3390/ijms151120169
|View full text |Cite
|
Sign up to set email alerts
|

Current Experience in Testing Mitochondrial Nutrients in Disorders Featuring Oxidative Stress and Mitochondrial Dysfunction: Rational Design of Chemoprevention Trials

Abstract: An extensive number of pathologies are associated with mitochondrial dysfunction (MDF) and oxidative stress (OS). Thus, mitochondrial cofactors termed “mitochondrial nutrients” (MN), such as α-lipoic acid (ALA), Coenzyme Q10 (CoQ10), and l-carnitine (CARN) (or its derivatives) have been tested in a number of clinical trials, and this review is focused on the use of MN-based clinical trials. The papers reporting on MN-based clinical trials were retrieved in MedLine up to July 2014, and evaluated for the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 256 publications
(410 reference statements)
1
22
0
Order By: Relevance
“…In Germany injected ALA is a prescription medicine to treat type II diabetes [16] [17]. On the other hand, clinical trials with ALA have failed to produce data that are consistent with the results reported by Xiong et al, although specific endpoints consistent with this report have not explored [18] [19] [20] [21].…”
Section: Medical Implicationssupporting
confidence: 75%
“…In Germany injected ALA is a prescription medicine to treat type II diabetes [16] [17]. On the other hand, clinical trials with ALA have failed to produce data that are consistent with the results reported by Xiong et al, although specific endpoints consistent with this report have not explored [18] [19] [20] [21].…”
Section: Medical Implicationssupporting
confidence: 75%
“…As predicted by Luft in 1994 [1], "mitochondrial medicine" has met a broad and growing flow of basic and clinical investigations, with extensive implications in a number of disorders related to several medical disciplines [2,7]. This is the case for both T2D and FA, through different pathogenetic mechanisms and background information, and pointing to the prospects of utilizing mitochondrial-targeted adjuvant treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the recognized roles of MNs in mitochondrial functions, a body of literature has focused on the beneficial outcomes of treating diabetic patients with each MN, leading to clinical improvements following patients' treatment with ALA, or coQ10, or CARN, as summarized in Table 1 (reviewed in [7]). Since early clinical studies in the 1990s, ALA has been demonstrated to provide adjuvant support in ameliorating the clinical conditions of T2D patients [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], with the recognition of ALA as a prescription drug in diabetic patients by the German Drug Index [49].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations